Evidence‐based rationale for low dose nivolumab in critically ill patients with sepsis‐induced immunosuppression - Demy A. C. van denHaak; Leila‐Sophie Otten; Hans J. P. M. Koenen; Ruben L. Smeets; Berber Piet; Peter Pickkers; Matthijs Kox; Rob ter Heine (Wiley, 2023)
Abstract A substantial part of critically ill patients suffer from sepsis‐induced immunosuppression. Reversal of immunosuppression through PD‐1 checkpoint inhibition has been proposed as a treatment strategy to overcome immunosuppression in these patients. The PD‐1 inhibitor nivolumab, currently used in treatment of cancer, has been evaluated in phase I/II studies in patients with sepsis, demonstrating tolerability and signs of clinical efficacy. No proper dose finding was performed in these studies and, after a single high dose of 480 mg or 960 mg nivolumab, PD‐1 inhibition persisted beyond 90 days in the majority of cases. As the duration of sepsis is ~7-10 days, prolonged PD‐1 inhibition may unnecessarily induce longer‐term immune‐related side effects. Based on previously published pharmacokinetic and pharmacodynamic data of nivolumab, a thorough in silico dose finding study for nivolumab in critically ill patients was performed. We found that volume of distribution and clearance of nivolumab were not higher in patients with sepsis compared to the cancer population for which nivolumab is currently approved and showed profound variability. We found that with a single dose of 20 mg nivolumab, the PD‐1 receptor occupancy is predicted to stay above the 90% threshold for a median of 23 days (90% prediction interval of 7-78 days). We propose to investigate this dose in critically ill patients as a potential safe and cost‐effective pharmacotherapeutic intervention to treat sepsis‐induced immunosuppression.